1996
DOI: 10.1042/bj3190507
|View full text |Cite
|
Sign up to set email alerts
|

Polynucleotide: adenosine glycosidase activity of saporin-L1: effect on DNA, RNA and poly(A)

Abstract: The ribosome-inactivating proteins (RIPs) are a family of plant enzymes for which a unique activity has been determined: rRNA N-glycosidase, which removes adenine at a specific universally conserved position (A4324 in the case of rat ribosomes). Here we report that saporin-L1, a RIP from the leaves of Saponaria officinalis, recognizes other substrates, including RNAs from different sources, DNA and poly(A). Saporin-L1 depurinated DNA extensively and released adenine from all adenine-containing polynucleotides … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
54
0
2

Year Published

1996
1996
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 74 publications
(61 citation statements)
references
References 27 publications
(32 reference statements)
5
54
0
2
Order By: Relevance
“…These effects are catalytic, as shown by molar ratio less than 1 between RIP present in the reaction mixture and adenine released. From the characteristics of their enzymatic activity, RIPs appear to be a non-homogeneous class of enzymes, in that (i) some release one, and some more than one adenine residues per ribosome [14], (ii) some are more active on poly(A) than on RNA [15,16] and (iii) have variable activity on RNA and on DNA (unpublished results). CIP-29 releases only one adenine residue from rat liver ribosomes, is not particularly active on poly(A), but is very active on DNA, more than any RIP assayed so far under the same experimental conditions.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…These effects are catalytic, as shown by molar ratio less than 1 between RIP present in the reaction mixture and adenine released. From the characteristics of their enzymatic activity, RIPs appear to be a non-homogeneous class of enzymes, in that (i) some release one, and some more than one adenine residues per ribosome [14], (ii) some are more active on poly(A) than on RNA [15,16] and (iii) have variable activity on RNA and on DNA (unpublished results). CIP-29 releases only one adenine residue from rat liver ribosomes, is not particularly active on poly(A), but is very active on DNA, more than any RIP assayed so far under the same experimental conditions.…”
Section: Resultsmentioning
confidence: 94%
“…RIPs were found to be peculiar N-glycosidases, and to remove a single adenine from a precise position in rRNA (A 4324 in the case of rat liver ribosomes) (review in [13]). More recently, however, it was reported that some, but not all, RIPs remove more than one adenine residue per ribosome [14], and that saporins [15,16] and other RIPs ( [12]; unpublished results by Barbieri et al) remove adenine from RNA other than rRNA and also from DNA. Consistently, ricin removes 2'-deoxyadenine from a synthetic dodecanucleotide with a GdA-GA loop, actually at a faster rate than it removes adenine from a similar dodecanucleotide with a GAGA loop [17].…”
Section: Resultsmentioning
confidence: 99%
“…For instance, it has been shown that several RIPs can release adenine from multiple sites in rRNA (5). Furthermore, saporin-L1 can release adenine residues from a variety of nucleic acid substrates, including poly(A), mRNA, tRNA, and DNA (6,7). More than 50 other RIPs are active on DNA (8).…”
mentioning
confidence: 99%
“…In addition to ribosomal depurination, some RIPs act on naked rRNA (rRNA devoid of ribosomal proteins); some remove multiple adenines and guanines from various nucleic acid substrates including DNA, poly(A), rRNA, and even viral RNA [29][30][31][32]. Viral RNA depurination is a matter that is worthy of attention.…”
Section: Activities Attributed To Papmentioning
confidence: 99%